Using Picture Series in Teaching Writing Skill for The First Semester Students of Medical Record Program in Stikes Bhakti Husada Mulia Madiun - Lidia Deviga; Yudha Fika Diliyana (Universitas PGRI Madiun, 2020)
The aim of this research was to find out the using series of pictures to improve the skill in writing recount text of first semester students of medical record program in STIKES Bhakti HusadaMuliaMadiun . This study was done on september 2019. The writer chooses the first semester class that consists of 45 students. The result of this study is expected to be useful for students, teachers, and further researchers, because the study will give contribution to improve students’ writing by using series ofpictures. The method that was used in this research was classroom action research.It was carried out in two cycles. The techniques for collecting data are planning, acting, observing, and reflecting. The subject of this study was the first semester student of medical record program of STIKES BHM Madiun During the research, the researcher acted as the teacher and acted as an observer during the implementation of series of pictures. She made reflection about what happened in cycle I. After that, she is re-planning the activities that were going to do in cycle II. The instruments used in this study were the writing test, observation sheet, questionnaire and interview.The data collected through writing test using minimum scored in written test were ≥ 70. If the results of the test ≥ 75%, students have score ≥ 70, it means that the research is success. And if the result of the test < 75%, students have score < 70, it means that the research is not success.After the result of the students’ test was analyzed, it showed that series of picture had improved the students’ writing ability. The result of the study from preliminary study showed that the students’ writing ability was quite poor. Whereas the result of the cycle I and cycle II indicated that the students who pass the test areincrease.The research findings were taken from cycle I and cycle II. The result of test 1 showed that 19 students got score less than 70 or 30% was unsuccessful and 26 students score more than70 or 70% was successful. The result of test II showed that 9 student got score less than 70 or 20% was unsuccessful and 36 students score more than 70 or 80% successful. It means that in cycle II the students’ score test got better and the research is success